COVID-19 Containment Measures at Childcare and Schools in 19 European Countries: An Observational Study on Local, Federal and National Policies - Danielle E. M. C. Jansen; Danielle E. M. C. Jansen; Johanna P. M. Vervoort; Károly E. Illy; Károly E. Illy; Adamos Hadjipanayis; Adamos Hadjipanayis (Frontiers Media S.A., 2021)
Objectives: After childcare and schools have been closed in March 2020 to prevent the spread of COVID-19, they were open again in most European countries after the summer holidays till early autumn. Aim of this study is to give an overview and to compare COVID-19 childcare and school containment policies in 19 European countries.Methods: We collected data on containment measures among delegates of the European Academy of Pediatrics (EAP), through an online, closed questionnaire in the second half of October 2020.Results: Most policy has been formulated for secondary education. In all three settings policy was most often formulated for individual hygiene, cleaning of surfaces, exclusion of sick children, ventilation, distance between children and between children and teachers. In secondary schools, policy is formulated on face masks in and outside the class. School closure, cancellation of physical education and class size reduction are measures for which the fewest countries have formulated national policies.Conclusion: We recommend to accompany the opening of children's facilities and schools by surveillance studies that further clarify questions about control measures implemented to halt COVID-19 pandemic.